Model Pembelajaran Discovery Berbasis Blended Learning untuk Meningkatkan Aktivitas dan Hasil Belajar Kimia Mahasiswa - Nurhamidah Nurhamidah; Nadia Amida; Rina Elvia (Universitas Pendidikan Mandalika Mataram, 2022)
Indonesia is one of the countries affected by the Covid-19 outbreak, where this situation greatly affects all aspects of life, including the field of education. The learning process is carried out online or in a network to minimize the spread of this virus, which makes learning effectiveness less than optimal, especially for material in the field of science. Selection of the right strategy and match the material is very necessary. The purpose of this study was to see the activities and learning outcomes of students using a blended learning-based discovery model on the subject of the Basic Laws of Chemistry. This research is a classroom action research conducted in two cycles. The research subjects were 26 students of the Biology Education Study Program in the first semester of the 2021/2022 class. The research data were obtained through observation sheets and cognitive tests using a test instrument in the form of a posttest. Based on the data analysis, it shows that the activities and student learning outcomes have increased from 54.62% and 66.25 in the first cycle to 87.69% and 80.48 in the second cycle. The students' understanding of the learning materials has included very good criteria.